¿Bienvenido y hasta luego u hola y adiós?: conductas comunicativas de los médicos residentes en los momentos iniciales y finales de las consultas() - Ruiz-Moral, R. (Aten Primaria, 2005)
OBJECTIVES: To describe the communicative behaviour by residents at the beginning (reception and first seconds after obtaining information) and closing of the consultation and to evaluate in what way very early interruptions in the patient monologue affect within-consultation results, such as the duration of their closing and the appearance of new concerns in this phase. DESIGN: Descriptive observational study. LOCATION: Primary care clinics. PARTICIPANTS: Thirty seven third year residents of family medicine and 307 patients with incidental problems. MATERIAL AND METHOD: All the consultations were videotaped and analysed by 2 trained observers who used previously validated established ad hoc procedures. RESULTS: The reception and closing of the consultations by the residents were very short and very poorly communicated since they used very few relational abilities. Half of the doctors redirected the initial discourse of the patient very early on (in 16 sec) and this was significantly associated (P=.03) with new concerns by the patient at the time of closing and with longer goodbyes (P=.001). CONCLUSIONS: The conduct of the residents in the moments studied surely limits their ability to establish and maintain a clinical relationship, to obtain information and explain what they are giving to the patients. The dysfunctional closures are most probable when the doctor assumes a dominant role very early: this behaviour does not shorten the consultations.